LGG-51. Resection extent and BRAF V600E mutation status determine postoperative growth velocity in pediatric Low-grade glioma: Results from a single-center cohort analysis. (3rd June 2022) - Gorodezki, David; Sosa, Jordana; Holzer, Ursula; Queudeville, Manon; Zipfel, Julian; Bevot, Andrea; Schittenhelm, Jens; Nägele, Thomas; Ebinger, Martin; Schuhmann, Martin
Abstract: Despite the favourable outcome and excellent long-term overall survival rates, pediatric LGG show vast variety of clinical behavior and limited predictability regarding progress or senescence. We comparatively analyzed the tumor growth velocity (TGV) of PLGG post subtotal resection (STR) to investigate the impact of surgery, histological subtype, tumor location and the most frequent BRAF aberrations (BRAF V600E mutation vs KIAA1549-BRAF fusion) on tumor growth rates, aiming to identify potential variables to prognosticate further progress or senescence. A total of 53 patients vs 94 patients in the pre- and postoperative cohort, respectively, could be observed over a mean follow-up time of 40.2 vs 60.1 months. Distribution of histopathological diagnosis and tumor sites showed similarity to previously published cohort studies. Comparative analysis of pre- and postoperative TGV showed a significant difference as mean preoperative TGV accounted for 0.264 cm³/mo, while postoperative TGV after 1st, 2nd and 3rd STR showed reduction to 0.085 cm³/mo, 0.024 cm³/mo and -0.016 cm³/mo, respectively (p < 0.001). Results remained significant after excluding patients who had obtained (neo)adjuvant treatment. Resection extent showed remarkable correlation with postoperative reduction of TGV (R = 0.97, P < 0.001). Comparison of postoperative TGV of BRAF V600E mutant LGG and BRAF wild-type LGG showed significant difference of means (0.123 cm³/mo and 0.016 cm³/mo, p = 0.47), consistent to previous analyses, suggesting BRAF V600E positive LGG as a high-risk subgroup. Histological type, tumor location and BRAF-KIAA1549 fusion showed no significant impact on postoperative TGV. The results suggest that surgery, beyond cytoreductive purpose, impacts PLGG kinetics post STR by inducing a significant deceleration of tumor growth. As postoperative growth velocity showed clear correlation to resection extent and residual tumor burden, surgery, as radical as possible while preserving neurological function, appears to remain the mainstay of therapy besides advancing therapeutic approaches.